Analysis of Attitude and Subjective Norm of Customers to Adopt Non Interest Banking in Nigeria: A Preliminary Study (Lapai Journal of Economics, 2019)
The main objective of this paper is to investigate whether the items of attitude toward adoption of Islamic banking and items of subjective norm are reliable and valid to predict the intention to adopt Islamic banking in Northern Nigeria. It is significant to know that attitude of customers to adopt Islamic banking and subjective norm are new in Islamic environment. Therefore, to test the capability of these variables is imperative in Islamic economics, Islamic banking, accounting, taxation and insurance. The paper found that attitude of customer towards the adoption of Islamic banking and subjective norm items are capable of predicting intention to adopt Islamic banking in northern Nigeria. The study used Cronbach alpha and found that the variables are reliable and valid. The paper establishes that items used in this preliminary study can efficiently be used in the main study.